Isolation and identification of microorganisms causing water-based paint and wall paint destruction - Van, Tran Thi Thanh; Cuong, Bui Van; Hong, Cao Thi; Huy, Nguyen Trung; Thai, Vu Quoc; Dung, Trinh Quang; Xuyen, Nguyen Thi; Anh, Vo Thi Kieu; `Trang, Nguyen Van; Lam, Tran Dai (Vietnam Journal of Science and Technology, 2022)
From samples of moldy wall paint and damaged water-based paint, we isolated and quantified the density of microorganisms present in the samples and determined the morphology of the isolates; thereby, identifying the genera of the bacteria and mold strains. The results showed that the density of the strains collected from the wall paint samples was much higher than that of the water-based paint samples (106 CFU/mL and 104 CFU/mL, respectively). In the wall paint samples, only mold colonies were observed, not bacterial colonies, while in the water-based paint samples both mold and bacterial colonies appeared, although mold colonies were still predominant. Based on the observation of colony formation and microscopic morphology of molds, we classified six mold strains into five genera: Aspergillus sp., Cladosporum sp., Acremoium sp., Chaetomium sp., and Fusarium sp. The frequency of strains belonging to the genus Aspergillus sp. accounted for the majority in both wall and water-based paint samples. Among the three bacterial strains isolated, we identified two bacterial strains as G (-) and one strain as G (+).